Drainage observations in poorly drained soils in the Atlantic zone - Maebe, P. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
9 fig. 5 tab. 2 ref. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 85